Production of high strength concrete using superplasticizer and addition of microsilica (Research, Society and Development, 2020)
High performance concretes have properties that satisfy several quality criteria such as strength, workability and durability. Strength is the most important measure of concrete quality, although many others can be taken into account. In the past, the basic rule for the production of high-strength concretes was the addition of more Portland cement and less water to the mixture, however mixtures rich in cement present greater retraction and greater possibility of cracking. The appearance of water-reducing additives significantly increased the strength of the concrete, in addition to mineral additions such as silica and fly ash of good quality also contributed greatly to this increase in strength. The objective of the research was to compare the mechanical properties of axial compression strength and tensile by diametrical compression of conventional concrete produced with natural aggregates from the Amazon region and concrete with special characteristics, high strength concrete, through the addition of microsilica and chemical additive superplasticizer, for ages 7, 14, 21, 28 and 90 days. The addition of microsilica reduced the porosity of the matrix, improving the interface with the aggregates of the mixture, while the superplasticizer allowed a substantial reduction in the hydration water, significantly increasing the strength of the concrete.